2013
DOI: 10.1161/circulationaha.112.000826
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Activated Protein-1 Transcription Factor JunD Induces Oxidative Stress and Accelerates Age-Related Endothelial Dysfunction

Abstract: Background-Reactive oxygen species are major determinants of vascular aging. JunD, a member of the activated protein-1 family of transcription factors, is emerging as a major gatekeeper against oxidative stress. However, its contribution to reactive oxygen species homeostasis in the vasculature remains unknown. Methods and Results-Endothelium-dependent vasorelaxation was impaired in young and old JunD(-/-) mice (6 and 22 months old) compared with age-matched wild-type mice. JunD(-/-) mice displayed an age-inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 46 publications
7
79
1
Order By: Relevance
“…JunD knockout mice display a vascular phenotype resembling accelerated endothelial aging with an impairment of endothelium-dependent vasorelaxation, disruption of mitochondrial function, and increased oxidative stress (43). Expression of JunD was significantly decreased in uremic aortas, supporting the concept of uremia being a state of premature aging.…”
Section: Uremicmentioning
confidence: 78%
See 1 more Smart Citation
“…JunD knockout mice display a vascular phenotype resembling accelerated endothelial aging with an impairment of endothelium-dependent vasorelaxation, disruption of mitochondrial function, and increased oxidative stress (43). Expression of JunD was significantly decreased in uremic aortas, supporting the concept of uremia being a state of premature aging.…”
Section: Uremicmentioning
confidence: 78%
“…Expression of JunD was significantly decreased in uremic aortas, supporting the concept of uremia being a state of premature aging. JunD protooncogene expression has not been previously demonstrated in the uremic calcified vasculature, but recently an age-dependent downregulation of JunD has been shown in the endothelium (43).…”
Section: Uremicmentioning
confidence: 91%
“…Many of these endogenous antioxidant pathways are controlled by the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2), which binds to the antioxidant response elements (ARE) in the promoter regions of genes to induce upregulation of antioxidant enzymes such as glutathione, manganese (mitochondrial) superoxide dismutase (SOD2), and heme oxygenase (86, 109). Recent work also indicates an important role for the activated protein-1 transcription factor JunD in regulating vascular superoxide, antioxidant pathways, NO bioavailability, and endothelial function with aging in mice (137).…”
Section: Critical Upstream Homeostatic and Stress Resistance Pathwaysmentioning
confidence: 99%
“…DAPK1 has been shown to be indispensable in cell death mediated by IFN-␥, transforming growth factor ␤ (TGF-␤), TNF-␣, DNA damage, and oxidative stress (reviewed in reference 35). JunD has a cytoprotective role in the response to oxidative stress in several cell types (36)(37)(38)(39)(40)(41). Preliminary analyses indicated that v-Src-transformed CEFs expressing TAM67 or the junD shRNA have elevated levels of reactive oxygen species (our unpublished results).…”
Section: Discussionmentioning
confidence: 79%